Integrated mathematical model of the transcribing system adapted to aviation conditions - B. I. Ogunwole; O. S. Kutepova (Научный вестник МГТУ ГА)
In this paper the authors have created the integrated mathematical model of the transcribing system adapted to aviation conditions, taking into account many factors. The paper analyses the following main problems of transcribing Englishlanguage speech between pilots and air traffic controllers (ATC) (radio exchange), namely: the tendency to use abbreviations and specialized vocabulary, which can cause misunderstanding for one of the parties; speech illegibility due to noise in the cockpit or in the radio frequency zone; insufficient clarity and accuracy in expressing instructions by air traffic controllers can lead to errors in the understanding and execution of instructions by pilots; limitations in the availability of communication channels and their overloading; lack of training in the use of English-language terms and expressions in the air traffic control system. Inadequate training in English language terms and expressions can lead to difficulties in understanding instructions and messages between pilots and air traffic controllers; differences in accents and pronunciation of communicators can also cause difficulties in speech comprehension. Aviation communication errors are critical to aircraft safety. The ambiguity of certain phrases or expressions in English can lead to misinterpretation and misunderstanding of instructions by controllers; lack of context or lack of information about the current situation on board the aircraft can make it difficult to transcribe speech and lead to misunderstanding of messages; use of slang or informal expressions can make transcribing English-language speech more difficult and cause misunderstandings; lack of opportunity to ask clarifying questions or request a real-time repetition of a message can lead to misunderstandings; and the use of slang or informal expressions can lead to misunderstandings. Even the most minor errors can have disastrous consequences. The analysis revealed that in the overwhelming majority of cases it is linguistic factors that cause misunderstandings between participants in radio conversations, which is evidence of the need to develop and improve this model.